Energy and Exergy Analysis in Combined Cycle Power Plant and Open Cycle Operating Conditions Effect on the Environment - Berkah Fajar Tamtomo Kiono; Tua Harolt Hutapea; Sutaryo Sutaryo (BIORE Scientia Publisher, 2025)
Efforts are required to save energy and utilize energy efficiently because of fossil fuel depletion. The purpose of this study is to determine the performance of the Tutong CCPP through a study of energy and exergy efficiency, also exergy losses analysis by determining four scenarios. Energy and exergy analysis using the Cycle Tempo program obtained the results of energy efficiency in scenario 1, which is 49.26%, almost the same as the energy efficiency in scenario 2, which is 49.1% where the CCPP operates with the same GT and ST loads but in scenario 2 the ST ASV experiences actuator damage. Scenario 3 obtained CCPP efficiency of 47.6% and scenario 4 obtained open cycle efficiency of 28.2%. The largest exergy loss occurred in the Condenser, which was 81.9% in scenarios 1 and 2 and 83.4% in scenario 3. From these results, it shown the greatest exergy loss occurred in scenario 3 where two ACC fans were not functioning, resulting in greater losses due to suboptimal vacuum. A significant exergy loss also occurs in the combustion chamber, which are 15.1%, 15.05%, 15.6% in scenarios 1, 2, 3 and also 16.7% in scenario 4. A large exergy loss in scenario 4 also occurs in the chimney, that is 16.7%.